Weekly training volume and hematological status in female top-level athletes of different sports - Ostojic, S. M.; Ahmetovic, Z. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The objectives of the present study were: a) to investigate the prevalence of iron depletion and anemia among female top-level athletes from different sports; b) to determine a relationship between serum ferritin levels and training status of female athletes. Methods. This study was conducted on 84 female professional athletes who were recruited during preparticipation physical examination. Upon entering the laboratory 10 mL of venous blood was drawn from an antecubital vein into a lavender-top tube for a complete blood count (CBC), serum iron, and transferrin and ferritin levels. Results. No significant differences between any of the hematological variables were found between groups of different sports. The lowest hemoglobin (Hb), mean corpuscular volume (MCV), serum iron, ferritin and transferrin encountered in the study were Hb of 9.1 g/dL, MCV of 64.5 fL, serum iron of 15 µg/dL, ferritin of 5.4 µg/L, transferrin of 210 µg/dL in a 20-year old female distance runner with functional impairment and iron deficiency anemia. No significant differences were found between female athletes from different sports regarding the prevalence of iron depletion, iron deficiency or iron deficiency anemia (IDA). Serum ferritin level poorly correlate with training duration (r = 0.24) and seems to be inadequate indicator of training tolerance. Conclusion. This study has shown a high prevalence of iron depletion and anemia among female athletes from different sports, with similar incidence in individuals independent of their weekly training volume.